(untitled) (African Journal of Public Administration & Management, 2026)
Develop clear written policies on ex- officio roles and compensation. Prefer non-monetary (training, awards) recognition Allow compensation only additional duties are proven Align with King IV, OECD, and emerging Zambian Code. 4th December 2025 Strengthen role of Board Secretaries as governance custodians.